The Political Economy of Generosity - On Sloterdijk's New Idea of Tax Regulation - Ratajczak, Mikołaj (Hybris, 2012)
The article deals with the debate that took place in the German press after the publication of Peter Sloterdijk's short, but provocative text "The Revolution of the Giving Hand" in 2009. The aim of this presentation is to show the insufficiency of the arguments raised against Sloterdijk's idea that the taxes should not be mandatory, but they should rather take on a form of a voluntary gift and a free contribution to the community. The debate was insufficient as far as it didn't address the philosophical aspect of Sloterdijk's idea - the problem of the overerotization of contemporary social life, its lack of the thymotic element: pride, generosity etc. and the destruction of social solidarity by the machine of the modern welfare state. If Sloterdijk's tax regulation idea is to be dealt with properly and criticised in its entirety, it must be first understood in its whole philosophical and political dimension.